Multi-species measurements of the firehose and mirror instability thresholds in the solar wind - Chen, C; Matteini, L; Schekochihin, A; Stevens, M; Salem, C; Maruca, B; Kunz, M; Bale, S (Institute of Physics, 2016)
Thefirehose and mirror instabilities are thought to arise in a variety of space and astrophysical plasmas, constraining the pressure anisotropies and drifts between particle species. The plasma stability depends on all species simultaneously, meaning that a combined analysis is required. Here, we present thefirst such analysis in the solar wind, using the long-wavelength stability parameters to combine the anisotropies and drifts of all major species(core and beam protons, alphas, and electrons). At the threshold, the firehose parameter was found to be dominated by protons (67%), but also to have significant contributions from electrons (18%) and alphas (15%). Drifts were also found to be important, contributing 57% in the presence of a proton beam. A similar situation was found for the mirror, with contributions of 61%, 28%, and 11% for protons, electrons, and alphas, respectively. The parallel electricfield contribution, however, was found to be small at 9%. Overall, the long-wavelength thresholds constrain the data well(<1% unstable), and the implications of this are discussed.